2017
DOI: 10.1007/s13524-017-0578-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-Heterosexuality, Relationships, and Young Women’s Contraceptive Behavior

Abstract: Non-heterosexual young women have a higher rate of unintended pregnancy than their heterosexual peers, but their fertility behaviors are understudied. We use longitudinal data from the Relationship Dynamics and Social Life study to investigate mechanisms contributing to non-heterosexual women’s higher pregnancy risk. These data include weekly reports of relationships, sex, and contraceptive use over 30 months. We compare the relationships and fertility behaviors of three groups: exclusively heterosexual (consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…Our sample of ever‐partnered 18‐ and 19‐year‐old women from the RDSL study resembles the nationally representative sample of 18‐ and 19‐year‐old women in the National Survey of Family Growth (NSFG), with a few exceptions . Black women are overrepresented in the RDSL study sample compared with the U.S. population (34% vs. 16%).…”
Section: Resultsmentioning
confidence: 99%
“…Our sample of ever‐partnered 18‐ and 19‐year‐old women from the RDSL study resembles the nationally representative sample of 18‐ and 19‐year‐old women in the National Survey of Family Growth (NSFG), with a few exceptions . Black women are overrepresented in the RDSL study sample compared with the U.S. population (34% vs. 16%).…”
Section: Resultsmentioning
confidence: 99%
“…12 Other published research compared the full RDSL sample to the nationally representative sample of the NSFG (Ela and Budnick 2017). African American women were overrepresented in the RDSL sample (34%) compared to the US population (16%).…”
Section: Resultsmentioning
confidence: 99%
“…37 In contrast, a recent study of New York City Youth Risk Behavior Survey data found that young SMW who identified as gay/lesbian or bisexual were more likely to report using no contraception at last sex compared with their heterosexual peers. 42 Additional data indicate that young SMW report less frequent contraceptive use 62 and use of less effective contraceptive methods compared with their heterosexual peers. 41 NSFG data reported by Agénor et al found that contraception use among adult women of all races who have sex with only women was less common (4.1-13.6%) as compared with their peers who have sex with men only (31.6-38.7%).…”
Section: Contraceptionmentioning
confidence: 99%